Pembelajaran Berkarakteristik Inovatif Abad 21 pada Materi Percaya Diri dengan Model Problem Based-Learning di SMK Negeri 1 Adiwerna - Heriyanti Rita (Cakrawala: Jurnal Pendidikan, 2022)
The purpose of this writing is to describe the development of innovative characteristics of the 21st century in confidence material in SMK Negeri 1 Adiwerna using a problem based learning model. Innovative learning in schools is a learning strategy that emphasizes the delivery of learning materials to students. This writing is motivated by demands in the 21st century that education should be able to produce human resources that are able to master the 21st century including, critical thinking, communicative, creteif and collaborative. The development of 21st century skills can be done by all disciplines, one of which is in guidance and counseling learning, educators can use problem based learning models. The method used in this writing is by studying literature by reviewing some literature for analysis and conclusions. The results of this paper conclude that problem-based learning models can be a solution in improving the innovative characteristics of the 21st century and confidence and motivate students to be more active and encouraged in their learning success.